Spermine Alleviates Acute Liver Injury by Inhibiting Liver-Resident Macrophage Pro-Inflammatory Response Through ATG5-Dependent Autophagy - Zhou, Shun; Gu, Jian; Liu, Rui; Wei, Song; Wang, Qi; Shen, Hongbing; Dai, Yifan; Zhou, Haoming; Zhang, Feng; Lu, Ling (Frontiers in Immunology, 2018)
Liver-resident macrophages (Kupffer cells, KCs) and autophagy play critical roles in the pathogenesis of toxin-induced liver injury. Recent evidence indicates that autophagy can regulate macrophage M1/M2 polarization under different inflammatory conditions. Polyamines, including putrescine, spermidine, and spermine (SPM), are polycations with anti-oxidative, anti-aging, and cell autophagy induction properties. This study aimed to determine the mechanisms by which SPM protects against thioacetamide (TAA)-induced acute liver injury in a mouse model. Pretreatment with SPM significantly alleviated liver injury and reduced intrahepatic inflammation in TAA-induced liver injury compared to controls. SPM markedly inhibited M1 polarization but promoted M2 polarization of KCs obtained from TAA-exposed livers, as evidenced by decreased IL-1β and iNOS gene induction but increased Arg-1 and Mrc-1 gene induction accompanied by decreased STAT1 activation and increased STAT6 activation. Furthermore, pretreatment with SPM enhanced autophagy, as revealed by increased LC3B-II levels, decreased p62 protein expression, and increased ATG5 protein expression in TAA-treated KCs. Knockdown of ATG5 in SPM-pretreated KCs by siRNA resulted in a significant increase in pro-inflammatory TNF-α and IL-6 secretion and decreased anti-inflammatory IL-10 secretion after TAA treatment, while no significant changes were observed in cytokine production in the TAA treatment alone. Additionally, the effect of SPM on regulation of KC M1/M2 polarization was abolished by ATG5 knockdown in TAA-exposed KCs. Finally, in vivo ATG5 knockdown in KCs abrogated the protective effect of SPM against TAA-induced acute liver injury. Our results indicate that SPM-mediated autophagy inhibits M1 polarization while promoting M2 polarization of KCs in TAA-treated livers via up-regulation of ATG5 expression, leading to attenuated liver injury. This study provides a novel target for the prevention of acute liver injury.